Optimalisasi Kegiatan Setting Function Pada Proyek Pembangunan Kapal Menggunakan Metode CPM dan PERT - Alika Kurnia Agustin; Hafid Syaifullah (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Planning project activities is one of the important foundations for project implementation so that the project can be carried out optimally. The schedule is part of project planning which is a parameter for the success of a project. Scheduling needs to be considered to determine the duration and sequence of project activities, so that a logical and realistic project schedule can be formed. The aim of this research is to obtain the critical path of a project activity along with the duration required during the project and to obtain the probability of the project reaching the expected target. In this research the Critical Path Method (CPM) and the Program Evaluation Review Technique (PERT) method are used. . Based on the results of the calculations and discussion, it can be concluded that in the function setting activity a critical path was obtained which consists of 7 activities, namely A – B – F – G – H – I – J with a duration of 57 days. It was also found that the probability of the project reaching the expected target within 76 days or less was 0.9978 or 99.78%.